2022
DOI: 10.5812/jssc.122867
|View full text |Cite
|
Sign up to set email alerts
|

Bruising and Bleaching Cosmetics

Abstract: : A review of the literature shows that bruises impair the aesthetic appearance of the skin. At the same time, official medicine has no cure for urgent skin discoloration in the area of bruises. Attention is drawn to the fact that alkaline hydrogen peroxide solutions effectively decolorize blemishes and the traces of blood by local interaction under in vitro and in vivo conditions. It has been shown that the main ingredients of these solutions are water, hydrogen peroxide, and sodium hydrogen carbonate. Some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…It was found that heating solutions of 3% hydrogen peroxide and 2 -10% sodium bicarbonate to the temperature of +37 -+45 • C, alkalizing them to pH 8.4 -8.5 and increasing the content of dissolved carbon dioxide gas or oxygen gas in them due to excess pressure gives them a unique physical and chemical activity. Due to this nonspecific physicochemical activity, WAHPSs have a unique local action on purulent masses (and other biological masses containing the enzyme catalase): pyolytic, bleaching, deodorizing, antihypoxic, oxygenreleasing, disinfecting, detergent and foaming action [50]- [53]. The results of laboratory and experimental studies have shown that irrigation of chronic wounds with WAHPSs and application of prolonged local hyperthermia in wounds shortens the removal of purulent masses from the wound surface and healing of chronic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that heating solutions of 3% hydrogen peroxide and 2 -10% sodium bicarbonate to the temperature of +37 -+45 • C, alkalizing them to pH 8.4 -8.5 and increasing the content of dissolved carbon dioxide gas or oxygen gas in them due to excess pressure gives them a unique physical and chemical activity. Due to this nonspecific physicochemical activity, WAHPSs have a unique local action on purulent masses (and other biological masses containing the enzyme catalase): pyolytic, bleaching, deodorizing, antihypoxic, oxygenreleasing, disinfecting, detergent and foaming action [50]- [53]. The results of laboratory and experimental studies have shown that irrigation of chronic wounds with WAHPSs and application of prolonged local hyperthermia in wounds shortens the removal of purulent masses from the wound surface and healing of chronic wounds.…”
Section: Discussionmentioning
confidence: 99%